Structural Change and the Freight Transport Labour Market - Blix, Mårten (OECD Publishing, 2017)
Nations that have managed to become rich have had institutional features that supported incentives for value creation while ensuring that the ways insiders and special interest groups can extract monopoly rents are limited. Improved skills have been a central component of helping individuals and societies to adapt to technological change. As technological progress has led to the disappearance of many difficult and arduous jobs, many new jobs have been created with higher skill content, leading to better productivity and real wage growth. In the long run, the modern economy is set to continue to create new jobs, especially in the service sector. But the required adjustments can lead to poor wage developments and social upheaval in the short-run. This is true for many sectors in the economy and especially so for the freight transport labour market. Technology could lead to strong disruption concentrated to particular groups, such as commercial drivers. Moreover, the effects may come in a more compressed period of time than previous periods of structural change, thus making it tougher for workers to adjust. Two types of policies to reduce the risks are to improve life-long learning and to reduce the risks associated with self-employment. Better education throughout working lives is the key to getting the benefits of technical change. Workers whose skills fall too far behind risk facing dimmer wage and job prospects. Could regulation aim to slow down the adoption of technical change over and above that motivated by safety concerns, thereby giving the labour market longer time to adapt? Such a policy would be harmful in the medium-to-long run. It would hold back productivity growth, which is the key to increased prosperity. Wage and job polarisation would likely also continue unabated
Keywords: Transport